Adaptive myopia. Part 2. New ideas on physiological mechanisms of eye’s focusing (Ukrainian Journal of Ophthalmology, 2026)
We reviewed morphology and physiology of macular zone of the eye and analyzed, adequately to the optics laws, an input optic signal from the white light coming into the foveola. The white light beam are dispersed at the outer corneal surface: these are not circles of scattered light but excitement bands of red and yellow cones in the foveola, and of blue cones on its circular periphery.We reviewed in detail the authors ' hypothesis on the presence of the fovea of the functional mechanism of “comparison of the location and intensity of the excitement fields of red, green and blue cones. This organization of the input optical signal allows the brain to create a response signal to control tone of ciliary muscles to install the required refractive power of the lens. Executive mechanism of the eye’s focusing is associated with operation in the fovea of the optical ring-sight consisting of dark blue cones with maximal possible concentration. Functional peculiarities of interaction of the rings-sights in binocular work of both eyes are identified.This hypothesis may have already helped detect the physiological mechanisms of the eye’s focusing and, apparently, in the future, would develop criteria for video security and visual work rules to fight against the pandemic of myopia. The work of found executive eye focusing mechanisms is considered by the authors in relation to their proposed hypothesis on metabolic theory of adaptation of myopia (2001). Until the rules of visual work are absent, the problems of video ecology and total prevention of acquired myopia are on the first place in the fight against the myopia pandemic.
Keywords: adaptation; acquired myopia; metabolic theory; early correction; visual acuity; video ecology; regulations for visual work; bands of excitation in the macula; mechanisms to control accommodation; axial length, and focusing